THE ROLE OF TEACHERS IN IMPROVING LEARNING INTEREST AND BUILDING STUDENTS' SELF-CONFIDENCE IN PAI LESSONS THROUGH CREATIVE TEACHING METHODS AT SDN SUMBEREJO - Anam, Muhammad Syaidul; Iqna’a, Julia; Mundiri, Akmal (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Islamic religious education teachers or PAI have a very strategic role in shaping the character and personality of students in accordance with the goals of national education, especially in fostering interest in learning and increasing self-confidence. The purpose of this study is to (1). Describe how the role of PAI teachers in increasing student interest in learning and building student self-confidence through creative teaching methods (2). Describe the influence of creative teaching methods applied by PAI teachers on changes in students both in terms of interest in learning and self-confidence to express themselves during the learning process. The research method used is a qualitative approach, namely research that produces descriptive data in the form of words with the type of field research. While data collection is through interviews and observations. The analysis method used is descriptive reflective thinking in presenting data, namely by drawing a conclusion.